BOSE-EINSTEIN CORRELATIONS OBSERVED IN E+E- ANNIHILATION AT A CENTER OF MASS-ENERGY OF 34-GEV - Althoff, M; Braunschweig, W; Kirschfink, F; Martyn, H; Rosskamp, P; Wallraff, W; Eisenmann, J; Fischer, H; Hartmann, H; Jocksch, A; Knop, G; Kolanoski, H; et al. (Springer-Verlag, 1986)
Bose-Einstein correlations between pairs of charged particles produced in e+e- annihilation into hadronic final states have been studied as a function of Q2, the relative momentum squared of the two particles in their centre of mass, and as functions of various pairs of kinematic variables. The observed Bose-Einstein enhancement reveals correlation between the position and time of particle emission, and the space-time structure of the source is shown to differ from that of a pion fireball. While most features of the data are well accounted for in terms of the space-time structure of a simple string model, the correlations are better described by the simple function 1+αe-βQ2. The implications of this result are discussed. The principal features of three particle correlations are explained in terms of the structure of the source inferred from the observed two particle correlations. © 1986 Springer-Verlag.